ANALYSIS OF FISHING PATTERNS AND SEASONS OF RED SNAPPER (Lutjanus sp.) LANDED AT PPP TASIKAGUNG, REMBANG REGENCY - Ulinnuha, Layali Alya; Hapsari, Trisnani Dwi; Fitri, Aristi Dian Purnama (Aurelia Journal, 2023)
One of the high-economic catches landed in Rembang district is red snapper (Lutjanus sp.). Red snapper is caught using bagged drag nets. Continued exploitation can threaten its sustainability. This study aims to determine the pattern and season of catching red snapper. The method used is descriptive method using purposive sampling and snowball sampling with 64 fishermen as respondents. Methods of data collection using observation, interviews, literature and documentation. Methods of data analysis using analysis of the value of  Catch per unit effort (CPUE),  Maximum Sustainable Yield (MSY), exploitation rate, effort level, and fishing season patterns are calculated using the average percentage method (average percentage method). The results showed that the CPUE value fluctuated with the highest value in 2020 of 1.456,12 kg/trip. The MSY value is 5.283.032 kg with an optimum effort value of 2.619 trips. The average utilization rate of 0,89 means that the red snapper resource has been (fully-exploited). The average red snapper effort level is 151,20% so that every year it is reduced. The peak fishing season is expected to occur in January, February, March, April, August, September, October and November.